In early returns scoring scores big. Issue 1 (July 2016) - Butman, Samuel M.
Key Points: A scoring or cutting balloon is always useful in preventing slippage during therapy of in‐stent restenosis. A drug‐coated scoring balloon for in‐stent restenosis may be an alternative to a drug‐coated balloon Definitive comparison trials are needed and likely to help define their exact role in patients with in‐stent restenosis